ANTIOXIDANT, ANTI-INFLAMMATORY, ANTIDIABETIC, ANTHELMINTHIC, AND THROMBOLYTIC ACTIVITY OF THE METHANOL EXTRACT OF CITRULLUS LANATUS PEEL - Nahar, Nazmun; Fatema, Ummul Khair; Sharma, Partha Protim; Bhuiya, Abdul Motaleb; Begum, Taslima; Azahar, Nur Fauwizah; Rahman, Mohammad Nasrin Abdul; Sulaiman, Wan Mohd Azizi Bin Wan; Azad, Abul Kalam (Universal Journal of Pharmaceutical Research, 2024)
Background: The present study aimed for in vitro evaluation of Citrullus lanatus Peel (CLP) methanol extract for antioxidative, anti-inflammatory, antidiabetic, anthelmintic, and thrombolytic activity. Method: CLP was extracted with methanol and tested for in vitro antioxidative (DPPH and H2O2 scavenging method), thrombolytic, anthelmintic, antidiabetic, and anti-inflammatory properties (human red blood cell membrane stabilization method, α-amylase inhibitory effect by using Iodine-Starch method. Results: The percentage yield was 7% and phytochemical profile showed the presence of steroid, tannins, saponins, flavonoids, glycoside and reducing sugar. In DPPH scavenging assay, 88.7% was at 1000 g/ml, whereas 34% to 48.9% (IC50 27.65 µg/ml) in H2O2 and from 61.8% to 95.2% (IC50 value: 07 µg/ml) in ASCOR. In in vitro anti-inflammatory activity, the maximum protection percentage was observed 58% and 44%. Consecutively, in anti-diabetic activity, IC50 values of 1137.64 μg/ml whereas reference (Acarbose) exhibited IC50 at 671.71 μg/ml. On the other hand, the inhibitory effect of Acarbose showed 57% and 98% respectively at 2000 μg/ml. In earthworms, it considered as very potential for the helminthic infection and helminthiasis. A significant clot lysis activity of 44% was noticed when the clots were treated with 100 µl of CLP extract (10 mg/ml) in in-vitro thrombolytic activity assay. Conclusions: The findings of this study revealed that the peel possessed the antioxidant, anti-inflammatory, antidiabetic, anthelminthic and thrombolytic activities. These findings will be motivated to do further research on molecular level to finds into more depth which is considered as the limitation of this study. Peer Review History: Received 3 February 2024; Revised 12 March 2024; Accepted 20 April; Available online 15 May 2024 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewers: Dr. Gehan Fawzy Abdel Raoof Kandeel, Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Dr. Francis Adou Yapo, Felix Houphouet Boigny, University of Abidjan, Ivory Coast, fyapo@yahoo.fr